2006
DOI: 10.1097/00000542-200610000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Hypoxemia in Children Is Associated with Increased Analgesic Sensitivity to Opiates

Abstract: Previous recurrent hypoxemia in OSA is associated with increased analgesic sensitivity to subsequent morphine administration. Therefore, opiate dosing in children with OSA must take into account a history of recurrent hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(172 citation statements)
references
References 7 publications
6
160
0
6
Order By: Relevance
“…This hypothesis is worthy of further studies given the circumstantial evidence that delaying administration of opioids might decrease morbidity. For example, researchers have shown that: half of the medical interventions performed to treat respiratory morbidity are needed within the first hour after tonsillectomy 15 ; children with obstructive sleep apnea have increased sensitivity to opioids; respiratory complications after adenotonsillectomy are often seen within two hours of opioid administration 15,16 ; and the need for major medical interventions to treat respiratory complications is reduced significantly when high-risk children undergoing adenotonsillectomy receive fewer opioids. 13 Therefore, while one could postulate that the opioid-sparing effects of dexmedetomidine might be desirable and beneficial to a highrisk population of patients with obstructive sleep apnea presenting for tonsillectomy, testing these hypotheses warrants further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is worthy of further studies given the circumstantial evidence that delaying administration of opioids might decrease morbidity. For example, researchers have shown that: half of the medical interventions performed to treat respiratory morbidity are needed within the first hour after tonsillectomy 15 ; children with obstructive sleep apnea have increased sensitivity to opioids; respiratory complications after adenotonsillectomy are often seen within two hours of opioid administration 15,16 ; and the need for major medical interventions to treat respiratory complications is reduced significantly when high-risk children undergoing adenotonsillectomy receive fewer opioids. 13 Therefore, while one could postulate that the opioid-sparing effects of dexmedetomidine might be desirable and beneficial to a highrisk population of patients with obstructive sleep apnea presenting for tonsillectomy, testing these hypotheses warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, researchers showed that children with obstructive sleep apnea appear to have increased sensitivity to opioids, and respiratory complications after adenotonsillectomies are often seen within two hours of opioid administration. 15,16 In addition, a recent retrospective study showed that the need for major medical interventions to treat respiratory complications was significantly reduced when high-risk children undergoing adenotonsillectomy received fewer opioids. 13 Therefore, taken together, these studies provide circumstantial evidence that an analgesic regimen that obviates, reduces, or delays the need for opioids is desirable and might reduce respiratory complications after tonsillectomies.…”
Section: Résumémentioning
confidence: 99%
“…Because of a lack of a uniform definition of obstructive sleep apnea (OSA) severity, the American Society of Anesthesiologists' latest guideline on perioperative management of OSA uses the terms mild, moderate, and severe "as defined by the laboratory where the sleep study was performed." If overall severity is not indicated by the sleep laboratory, they classify OSA severity from Apnea-Hypopnea Index (AHI) as none (0 -5), mild (6 -20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), severe (Ͼ40).…”
Section: Pathophysiologymentioning
confidence: 99%
“…24 -26 Adult and pediatric patients with OSA have been found to be highly sensitive to narcotics. 27,28 One study of children found that those with OSA required approximately half as much morphine for pain relief as children without OSA, likely because of increased sensitivity to opioids caused by recurrent hypoxic episodes. Central sleep apnea is much less common than OSA among postoperative patients.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Many such children have sleep-disordered breathing, and children with sleep-disordered breathing are known to be more sensitive to opioids. 4 Therefore, the FDA recently required that the manufacturers of all codeine-containing products add a boxed warning to the labeling of their product that describes the risk posed by codeine after a child has undergone tonsillectomy or adenoidectomy. A contraindication will be added to restrict codeine use in such patients.…”
mentioning
confidence: 99%